Lithium nickel oxyfluoride (Li1-zNi1+zFyO2-y) and lithium magnesium nickel oxide (Li1-z(MgxNi1-x)1+zO2) cathodes for lithium rechargeable batteries: II. Electrochemical investigations - Naghash, A.R. (2014)
10.1016/S0013-4686(01)00452-2